Studi Perbandingan Hasil Belajar Siswa Menggunakan Model Pembelajaran Contextual Teaching Learning dengan Model Pembelajaran Group Investigation di SMP - Mukhlasin, M. Sirojul; Edie, Sukiswo Supeni; Hindarto, Nathan (UPEJ Unnes Physics Education Journal, 2017)
Learning outcomes are the ability possessed wich are knowledge, attitude, and skills. The learning model of Contextual Teaching and Learning (CTL) involves students in activities that relate academic lessons to the context of life. The learning model of Group Investigation (GI) trains students to participate in social systems. This study aims to find out which between the learning model of CTL and learning model of GI that the results of learning are better. The population is the students of class VIII SMP Islam YPI Buaran Pekalongan. The sample used is VIII A as CTL class and VIII B as GI class. The data were collected by using the test to obtain the students' learning result of the cognitive domain, the questionnaire was used to obtain the affective domain learning result, and the observation sheet was used to obtain the psychomotor domain learning result. The learning outcomes of the CTL class students were lower than that of the GI class indicated by the results of the t-test polled variance test. Based on these results it can be concluded that the GI learning model is better than the CTL learning model.